Effects of Herbicide Application on the Soil Seed Bank in the Bekol Savanna of Baluran National Park - Muis, Nurmuliayanti; Setyawati, Titiek; Tjitrosoedirjo, Soekisman; Ratnadewi, Y. M. Diah (Indonesian Journal of Ecology and Conservation, 2024)
The dominance of broadleaf weeds after A. nilotica control resulted in a decrease in the dominance of grass species in the savanna area of Bekol BNP. Herbicide application for controlling broadleaf weeds is an effective and efficient method. However, the impact of herbicide use on seed storage in the soil is unknown, while seed storage plays an important role in the sustainability of vegetation. This study used a completely randomized factorial design with three factors: soil depth, type of herbicide, herbicide concentration, and a control (without herbicide application). The effect of herbicide application on seed germination was analyzed using ANOVA. The results of this study indicated that the application of herbicides had no significant effect on seed germination in the soil (P > 0.05). Therefore, the use of triclopyr and fluroxypyr herbicides could be considered as one of the measures for controlling broadleaf weeds in the savanna area of BNP.